The Best Police Election Decision Support System Using The SAW Method In SPN North Sumatra - Zulhami Abdi; Roy Fanry Siahaan (DISTANCE: Journal of Data Science, Technology, and Computer Science, 2021)
The Decision Making Process for the Selection of the Best Police NCO Selection Decision Support System Using the SAW Method at the SPN North Sumatra is currently still being done manually. In Determining the Selection of National Police Officers Who Have Criteria for Education, Health, Personality, High IQ (Psychology), Psychological and Physical. Where In Selection There Are Still Often Some Candidates For Police Officers Who Are Received Not By What They Want. In Determining the Selection of Candidates for NCOs, the Police Can Use a Decision Support System. The Research Method Used Is The Simple Additive Weighting Method. The result of this research is to find out that education, health, personality, high IQ (psycho test), psychology, and body influence in determining the selection of police officers.